(untitled) (International Journal of Ayurveda and Pharma Research, 2019)
Autism is most common mental disabilities in childhood with unknown aetiology nowadays. In our Siddha paediatric text, the symptoms of Mantha sanni are nearly correlated with Autism Spectrum Disorder (ASD). Objectives: The Main objectives of the study is to evaluate the Siddha therapeutic management and to analyse the clinical assessment of Mantha sanni (Autism Spectrum Disorder) with Experimental formulations and procedures and the secondary objectives are to calibrate the resemblance and the equivalence of Mantha Sanni with Autism Spectrum Disorder and to explore the Siddha therapeutic management in Autism children. Methods: In preclinical studies of Physicochemical, Phytochemical activities and Pharmacological activities were done. In clinical studies, among 30 children were included in inclusion criteria and received Kuruver kudineer as internal twice a day and Sambrani thuvalai and Mysatchi pugai as external once in a day. The Experimental period was 90 days and the activities of ASD children were recorded 0th day followed by every 30th day. Results and Discussion: In this clinical study indicating that both internal and external medicine had superior action as far as improvement in ASD is considered. Since Kuruver Kudineer use is to enhance cognitive skills, enhance nerve impulse transmission, research has been focused on the mechanism behind this activity. Thuvalai with Sambrani ennai use to enhance the Sitting tolerance, invigorating feeling and can give comfort. Fumigation with Mysatchi pugai is one of the methods of treatment in ancient period. It has to enhancing the mind calming activity, reduced hyperactivity, induced sound sleep, reduced screaming and irritable cry. In Statistical analysis, there is significant difference between before and after treatment on clinical assessment parameter score i.e. 86% improvement in this score after treatment. Based on the results of this clinical study, it can be conclude that Kuruver kudineer as internal and Sambrani thuvalai and Mysatchi pugai as external. It has a definite action as well as clinical efficacy on symptoms in ASD children seen in regular OPD and IPD. The effects of Internal and external therapies may be due individual drugs multipronged action. Further study is required for scientific validation to prove its clinical efficacy in multicentre clinical study.